Looking into the eyes of those we serve: Toward complex equality in public administration ethics - Saban, Ireni (2011)
This article adds to the debate on ethical issues surrounding public administration practice by an analysis of integrating partialities into impartial moral reasoning under two formalized theories of social justice. Such ethical deliberation takes a closer than usual look sat the moral complexity of public administration practices of partiality. The validity of adopting partiality as a possible principle to guide ethical decision making in public administration will be examined within the broader theories of social justice and how it conforms to social justice criteria. The article concludes by showing how new ethical ordering of partiality and kmpartiality, supplemented by Walzer's spherical justice, provides a systematic method for considering partialities in public administration decision making - Reproduced.
Keywords: Social justice; Ethics; Public administration